1970
DOI: 10.3329/bvet.v27i2.7559
|View full text |Cite
|
Sign up to set email alerts
|

Culture of <i>Brachionus plicatilis</i> feeding with powdered dried <i>Chlorella</i>

Abstract: The rotifer Brachionus plicatilis was cultured with powdered dried Chlorella in treatment 1, live or fresh cultured Chlorella in treatment 2, and baker's yeast in treatment 3. All the jars under three treatments were stocked with B. plicatilis at the initial density of 10 individuals per ml. The water temperature, air temperature, pH and dissolved oxygen were within the suitable range for B. plicatilis culture. The highest population densities of B. plicatilis in treatments 1, 2 and 3 were 60000, 50000 and 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…; Mostary et al . ). Moreover, the larval seabream Sparus aurata achieved a similar growth rate by feeding rotifers enriched either by live or dry N. gaditana (Cañavate & Fernández‐Dı́az ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Mostary et al . ). Moreover, the larval seabream Sparus aurata achieved a similar growth rate by feeding rotifers enriched either by live or dry N. gaditana (Cañavate & Fernández‐Dı́az ).…”
Section: Discussionmentioning
confidence: 97%
“…In hatchery, the unexpected crash of algal cultures will impact the live feed supply to zooplankton and negatively influence the fish production in hatcheries (Mostary et al . ). We found that the nutritional quality of copepods fed on dried algae was comparable to those fed on fresh algae especially in the EPA and DHA contents in coepods.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Alternativamente, como lo indican los datos de la composición proximal y contenido energético de las dietas; las semejanzas registradas, pudieron deberse al contenido de cantidades similares de lípidos y energía, mientras que las discrepancias se debieron probablemente a las diferencias en el contenido de proteínas, con mayor énfasis en la razón proteínas/lípidos, puesto que Øie & Olsen (1997) reportaron que existe correlación positiva entre la tasa de crecimiento y el contenido de proteínas y la razón proteínas/lípidos de los rotíferos. Adicionalmente, las dietas Espirulina y Rotimac son microalgas secas que tuvieron menores valores en los valores de dinámica poblacional, lo cual es coincidente con los resultados encontrados en otros trabajos, donde reportan que las dietas secas inducen bajas tasas de crecimiento (Mostary et al, 2010).…”
Section: Discussionunclassified